NATIONAL SECURITY AND THE DYNAMICS OF GLOBAL INSTABILITY: THE NATIONAL SECURITY STRATEGY OF THE REPUBLIC OF SERBIA AND NEW SECURITY CHALLENGES - Malbašić, Zoran; Trbojević, Milovan (National interest, 2026)
The national security of the Republic of Serbia in the third decade of the 21st century is conditioned by the accelerated dynamics of global instability and the multidimensional transformation of security challenges, risks, and threats that transcend classical state-centric frameworks and expand into non-traditional security domains. The authors suggest that, although the National Security Strategy of the Republic of Serbia (2019) seeks to provide a strategic and institutional response to the growing complexity of transnational risks-such as hybrid and asymmetric threats, terrorism, organized crime, migration, and climate change-it nevertheless exhibits significant conceptual limitations in the perception, detection, and treatment of contemporary security phenomena, including pandemics of infectious diseases, cybersecurity, digital sovereignty, and the security implications of the excessive use and misuse of artificial intelligence. This paper argues that Serbia’s national security policy should be optimised through the introduction of the widened security concept, which aims to integrate military and non-military dimensions-political, economic, societal, environmental, and technological-with the objective of ensuring a long-term adaptive system capable of proactively safeguarding national interests in a global order increasingly characterised by multipolarity and the transformation of traditional security challenges.